Mitigating shadowing effects through cluster‐head cooperation techniques. Issue 2 (1st June 2013) - Bithas, Petros S.; Lioumpas, Athanasios S.; Alexiou, Angeliki
Abstract : In many situations the performance of wireless communication systems decreases especially when they operate over multipath fading channels subject also to shadowing. In this sense, cluster‐based networks have been introduced as an efficient solution, offering coverage extension and energy saving. In this study, the authors investigate new cluster‐head (CH) selection algorithms, where the nodes can select different CHs, according to the corresponding signal strength. In addition, it is shown that if CHs are equipped with multiple antennas, the negative consequences of fading/shadowing can be further reduced. The performance of this scheme is theoretically investigated over correlated Nakagami‐ m fading channels, which are also subject to shadow fading, modelled by gamma distribution. The derived statistical metrics are used to obtain numerical evaluated results for the outage and the average bit error probabilities. These results are complemented by computer simulated ones, which validate the accuracy of the proposed analysis.